2013
DOI: 10.4238/2013.january.24.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of random regression models to estimate genetic parameters for milk production in Guzerat (Bos indicus) cows

Abstract: ABSTRACT. Random regression models have been widely used to estimate genetic parameters that influence milk production in Bos taurus breeds, and more recently in B. indicus breeds. With the aim of finding appropriate random regression model to analyze milk yield, different parametric functions were compared, applied to 20,524 test-day milk yield records of 2816 first-lactation Guzerat (B. indicus) cows in Brazilian herds. The records were analyzed by random regression models whose random effects were additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
6
10
2
Order By: Relevance
“…The magnitude of the heritability estimates found in the present study is similar to those reported by Olori et al (1999), Cobuci et al (2005), and Bignardi et al (2009) for the Holstein breed. Similar results (0.20 to 0.33) were found by Santos et al (2013a), who used RRM with parametric functions for Guzerat breed. When RRMs were used with parametric functions in Gyr dairy cows, Herrera et al (2008) found similar estimates to those found here.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The magnitude of the heritability estimates found in the present study is similar to those reported by Olori et al (1999), Cobuci et al (2005), and Bignardi et al (2009) for the Holstein breed. Similar results (0.20 to 0.33) were found by Santos et al (2013a), who used RRM with parametric functions for Guzerat breed. When RRMs were used with parametric functions in Gyr dairy cows, Herrera et al (2008) found similar estimates to those found here.…”
Section: Resultssupporting
confidence: 76%
“…(Tables 3 and 4). The genetic correlation estimates obtained with the RRMs were high and near the unity for the adjacent records, with the values declining as the interval between the test-day records increased (Tables 3). The same tendency was reported by Bignardi et al (2009) for the Holstein breed, by Kettunen et al (2000) for the Ayrshire breed, by Herrera et al (2008), and Pereira et al (2013b) for the Gyr breed, and Santos et al (2013a) for the Guzerat breed, all of them using parametric function. The three RRMs (Leg.3.5.6, Leg.3.6.6 and Leg.6.6.6) showed negative genetic correlation estimates between milk yield in the first and in the last test-day records, but of small magnitudes.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Genetic correlations (Table 1) between monthly milk yields ranged from -0.03 to 0.95 and the lowest or negative estimates occurred between yields at the beginning and end of lactation. Similar results have been reported by SANTOS et al (2013) for Guzerá cattle. Phenotypic correlations (Table 1) were all positive and ranged from 0.18 to 0.81.…”
Section: Resultssupporting
confidence: 80%
“…Production continued in the second month of lactation (8.98±4.14kg) and subsequently decreased after the third month until the end of lactation (5.44±2.53kg). The heritabilities of TDMY (Table 1) were higher than those reported by SANTOS et al (2013) for the same breed. These authors estimated a higher heritability in the second month (0.35) and a lower heritability in the eighth month of lactation (0.18).…”
Section: Resultsmentioning
confidence: 43%